Analisis Pemahaman dan Kesulitan Siswa pada Materi Peluang di Kelas XII SMA Negeri 1 Tanjung Morawa - Kairuddin Kairuddin; Nabila Mutiara Syifa; Nadhira Eka Putri Prayudi; Putri Syahbilah; Syalwa Nur Alisya; Annisa Saktiono; Fitrah Ifandi Hasibuan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to analyze students' understanding and difficulties in probability in grade XII of SMA Negeri 1 Tanjung Morawa and identify the contributing factors. The research method used is descriptive with quantitative and qualitative approaches. Quantitative data were obtained from the results of the problems given to students, then analyzed to determine the level of understanding, types of errors, and the percentage of difficulties experienced. Meanwhile, qualitative data were obtained through interviews with subject teachers to deepen information regarding the obstacles faced by students and the learning strategies implemented. The results showed that most students experienced difficulties in determining the sample space, applying probability formulas, and interpreting calculation results. Contributing factors include limited understanding of basic concepts, a lack of variety in practice questions, and learning that still focuses on procedures. Based on these findings, the researcher offers solutions in the form of contextual learning, conceptual reinforcement through class discussions, and the provision of step-by-step practice questions with teacher guidance. This research is expected to contribute to teachers in improving the effectiveness of probability learning in schools.